An analysis of the monetary transmission mechanism of M&A, Greenfield FDI, Domestic Investment, and GDP per capita growth: The structural vector correction model in Indonesia - Albert Hasudungan; Andrey Hasiholan Pulungan (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The study aims to evaluate the different implications of mergers and acquisitions (M&A) and Greenfield foreign direct investment in the transmission mechanism effects on the growth of gross domestic product per capita (GDP per capita) in Indonesia. The origin of the study stems from past academic debates that contested whether Greenfield FDI or M&A bear more effect on the economic growth in emerging markets. Design/methodology/approach: The study deployed a structural vector error correction (S-VECM) time series model to evaluate the short-term and long-term effects of M&A and Greenfield investment effects on the growth of GDP per capita in Indonesia. The research gathered secondary time series data from the first quarter of 2003 until the fourth quarter of 2019. The stages of the economic regression consisted of a stationary test, a co-integration test, an impulse response assessment, and a variance decomposition analysis. Finding: The study discovered the significance of the short-term effect of M & M&A to stimulate greenfield investment, which then ramps up more domestic investment and GDP growth. However, greenfield investment galvanised a stronger intermediary effect to augment GDP growth per capita over the long-term. This study remarks greenfield investment as the essential mediator to enhance domestic investment and GDP growth in long-term horizon Research limitations/implications: The study stems from past academic discussions that widely tested the exogenous effects of M&A and Greenfield investment on economic growth by pooling heterogeneous developing and developed countries. This study specifically removed the heterogeneous effects and added an endogenous analysis by devising S-VECM in Indonesia. However, this specific case study cannot reflect the association in other countries in Southeast Asia. More replicated studies can be undertaken on other Southeast Asian countries. Originality/value: Firstly, the academic contribution of this research mediates the past academic debates about the relative importance between M&A and Greenfield to drive economic growth. This study demonstrates the complementary functions of M&A and Greenfield in different time horizons, respectively in long-term and short-term time horizons. The study synthesizes more negotiating economic considerations of both M&A and Greenfield investment to affect economic development in different economic horizons. Secondly, this study enriches the econometric analysis by echoing the greenfield investment as the mediator function to stimulate domestic investment and GDP growth per-capita from the shock of M&A. from the transmission mechanism is on order initiated shock from M&A, Greenfield investment, domestic investment and then to the growth of GDP per capita. This mechanism transmission was not available in the past academic debates with the panel econometric studies.
Keywords: F20; F21; F47; 330; M&A; Greenfield; FDI; GDP per Capita Growth; Indonesia